Maternal-fetal obstetric outcomes in mothers of advanced maternal age: a cross-sectional analytical study at Saint-Joseph Hospital and the University Clinics of Kinshasa in the Democratic Republic of Congo - Tshimbundu Kayembe, Antoine; Kapinga Mutshiaudi, Anne; Mutombo Baleka, Alex; Mbangama Muela, Andy; Raschid Tozin, Rahma; Mbungu Mwimba, Roger; Sengeyi Mushengezi, Dieudonné; Kahindo Muyayalo, Patrick (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Pregnancy in advanced maternal age is any pregnancy occurring after the age of 35. Both late-term and early pregnancies carry a high risk of maternal and fetal morbidity and mortality and are a public health concern. The objective of this study is to identify obstetric outcomes associated with pregnancies in advanced maternal age at Saint-Joseph Hospital and the University Clinics of Kinshasa in the Democratic Republic of Congo. Methods: This is a cross-sectional analytical study of the records of mothers aged 16 to 50 who gave birth in the maternity wards of Saint-Joseph Hospital and the University Clinics of Kinshasa from 01 January 2018, to 31 December 2022, using non-probability convenience sampling for case selection. Descriptive analyses, analysis of variance (ANOVA), Chi-square tests and logistic regression were used in statistical analyses. Results: Pregnancies in women with advanced maternal age (AMA) are associated with the risk of pre-eclampsia (aOR: 2.5, p=0.02 for women aged 35-39 and aOR: 3.5, p=0.001 for those over 40) and gestational hypertension (aOR: 12.3, p=0.025 for those over 40), and fetal outcomes associated with pregnancies in women with AMA are prematurity (aOR: 2.7, p=0.001 for women aged 35-39 and aOR: 2.4, p=0.002 for women over 40), low birth weight (aOR: 2.5, p=0.0000 for women aged 35-39 and aOR: 2.4, p=0.002 for women over 40), and low birth weight (aOR: 2.5, p=0.0000 for women aged 35-39). women over 40 years of age) and admissions to neonatal intensive care units (aOR: 2.5, p=0.004 for women over 40 years of age). Conclusions: Obstetric outcomes associated with pregnancy in older mothers are preeclampsia, prematurity, low birth weight, and admissions to neonatal intensive care units. Our results are useful for prevention through screening and other therapeutic measures of these obstetric and neonatal outcomes in women with AMA with a view to improving their care in our hospitals in Kinshasa.